Ultra-broad band supercontinuum produced by terawatt femtosecond laser - 张伟力 王清月 邢岐荣 柴路 K.M.Yoo (Science China. Mathematics, 1997)
The characteristics of supercontinuum produced by high-intensity femtosecond pulses were investigated under different interaction lengths, various pump intensities, different pump wavelengths at the fundamental 800 nm and its second-harmonic 400 nm. High transfer-efficiency supercontinuum with flat-top in liquid media was produced. As the main nonlinear mechanisms, the effects of self-phase modulation (SPM) and four-photon parametric emission were also investigated.